Functional comorbidities and brain tissue changes before and after lung transplant in adults - Vandiver, Matthew Scott; Roy, Bhaswati; Mahmud, Fahim; Lavretsky, Helen; Kumar, Rajesh (Frontiers in Cellular Neuroscience, 2022)
Abstract Background: Adults undergoing lung transplant, as a lifesaving treatment for end stage lung disease, exhibit high levels of peri-operative neurocognitive dysfunction in multiple domains, including delirium, cognition, and autonomic deficits. These complications impact healthcare costs, quality of life, and patient outcomes. Post-operative symptoms likely result from loss of brain tissue integrity in sites mediating such regulatory functions. Our aim in this study was to examine peri-operative neurocognitive dysfunction and brain tissue changes after lung transplant in adults. Methods: We retrospectively examined the UCLA lung transplant database to identify 114 lung transplant patients with pre-operative clinical and neurocognitive data. Of 114 patients, 9 lung transplant patients had pre- and post-transplant brain magnetic resonance imaging. Clinical and neurocognitive data were summarized for all subjects, and brain tissue volume changes, using T1-weighted images, before and after transplant were examined. T1-weighted images were partitioned into gray matter (GM)-tissue type, normalized to a common space, smoothed, and the smoothed GM-volume maps were compared between pre- and post-transplant (paired t-tests; covariate, age; SPM12, p<0.005). Results: Increased comorbidities, including the diabetes mellitus (DM), hypertension, kidney disease, and sleep disordered breathing, as well as higher rates of neurocognitive dysfunction were observed in the lung transplant patients, with 41% experiencing post-operative delirium, 49% diagnosed with a mood disorder, and 25% of patients diagnosed with cognitive deficits, despite incomplete documentation. Similarly, high levels of delirium, cognitive dysfunction, and mood disorder were noted in a subset of patients used for brain MRI evaluation. Significantly decreased GM volumes emerged in multiple brain regions, including the frontal and prefrontal, parietal, temporal, bilateral anterior cingulate and insula, putamen, and cerebellar cortices. Conclusions: Adults undergoing lung transplant often show significant pre-operative comorbidities, including diabetes mellitus, hypertension, and chronic kidney disease, as well as neurocognitive dysfunction. In addition, patients with lung transplant show significant brain tissue changes in regions that mediate cognition, autonomic, and mood functions. The findings indicate a brain structural basis for many enhanced post-operative symptoms and suggest a need for brain tissue protection in adults undergoing lung transplant to improve health outcomes. Keywords: Perioperative Neurocognitive Dysfunction, Depression, Anxiety, Delirium, Magnetic Resonance Imaging.